Changes in the 6-minute walk test in patients in the cardiac rehabilitation program - Arboleda Campo, Victor Hugo (2026)
Introduction. In cardiac rehabilitation, the 6-minute walk test is a valid and reliable test to evaluate the submaximal functional capacity of cardiac patients, in guiding training modalities and establishing the prognosis of morbidity and mortality. Methodology. Retrospective study with review of medical records belonging to a clinical institution in a city in southwestern Colombia; anthropometric and physiological variables were examined, as well as the 6-minute walk test that completed the evaluations at the beginning and at the end of the 36-session program. Results. A sample of medical records of 41 participants with an average age of 66,8 years was included, of which 75,6% were men, with 41,3% limitations in physical performance; the presence of symptoms of depression and anxiety of 82,9 and 75,6 respectively; a difference in the distances compared to approximately 110 m of difference significantly p<.001 between the tests at the beginning and end of 36 sessions of the cardiac rehabilitation. Conclusion. During the walk, signiﬁcant changes are evident in relation to the routes traveled, with changes in vital signs that can be linked to good tolerance to the 6MWT effort and probable improvement in functional capacity.